Union Ritz (M) Sdn Bhd / Ariff Aiman Azmin Mustam ... [et al.] - Azmin Mustam, Ariff Aiman; Sulaiman, Muhammad Hafiz; Azmimera, Muhammad Zainurmera; Radzi, Hafizullah (2021)
UNION RITZ Sdn. Bhd. is a partnership business that focusing in the selling, supply and distribution of oil while doing the construction of a mini pump station in rural areas across Malaysia. We want to ensure that oil supply can be obtained especially in rural areas. This will open up the economy more competitive and rapidly due to the availability of facilities such as our gas station. Through this report of business plan, we will gave an overview of an outline of the establishment, including a full operational guide as described, in addition to securing an authorized loan for our business We were work together to develop and grow the business in order to provide a return to society and especially to the benefit of business. Therefore, we need to be more concerned and aware of the demands of the locals. It is crucial for a business to define the target market so that they should correctly estimate the number of current and prospective buyers on the market who will actually be buying the product sold by the company, since they are the ones that will generate profits and will pay tribute to our company's business. After conducting some research, we estimated that there are around more than 5,000 people approximately that live in Tanjung Karang, Selangor. Therefore, our company have devised a strategy to make a segmentation market strategy to boost our sale and market value. Firstly, we focusing on demographic segmentation which is we targeting at oil terminal to reduce our transportation cost and saving time. Then, we concentrate on psychographic segmentation which is based on the personality, motives, lifestyle and demographically factors. People are like to travel far away from the main city are hard to find gas station. It will help them especially to society and locals.